Análise comparativa da energia injetada na rede por inversores módulos CA utilizados em sistemas fotovoltaicos - Kunzler, Luccas Matiuzzi (2013)
This Master's Dissertation aims to compare two topologies of AC Module converters, applied in photovoltaic systems. The principles of operation, the characteristic equations, the parameters found are detailed for both topologies, while their transfer functions are analyzed in order to present optimized controllers. Commercial components are determined for the real system simulation, based on the same criteria for both AC Modules. The analysis of the energy injected in the grid by each topology and their respective cost with active components provides a quality index that allows a fair comparison between them and determining which topology provides superior performance on the conditions of this study. Through this index is observed that the efficiency of the converter Full-Bridge ZVS Phase Shift AC Module is superior. Experimental results of the converter are presented validating the theoretical analysis and the operation of the topology. The application of this topology is on photovoltaic systems and enables the use of these systems at small scales and with great potential for expansion. The use of photovoltaic energy is of utmost importance in the global scenario, where the search for renewable energy grows exponentially.